Revision of GUM: the suggested alhorythm for processing measurment results - Zakharov, I. P.; Neyezhmakov, P. I.; Botsiura, O. A. (My University, 2019)
The main requirements for the revised GUM are considered. The proposed algorithm for processing measurement results is given. Criteria for compliance with the listed requirements are described. Methods for processing the measurement results with a nonlinear model are proposed.
Keywords: GUM revision; estimates and standard uncertainties of input quantities; correlation; expanded uncertainty